Fate of anthropogenic cyclic volatile methylsiloxanes in a wastewater treatment plant. (1st April 2015) - Wang, De-Gao; Aggarwal, Monica; Tait, Tara; Brimble, Samantha; Pacepavicius, Grazina; Kinsman, Laura; Theocharides, Mike; Smyth, Shirley Anne; Alaee, Mehran
Abstract: The fate of cyclic volatile methylsiloxanes (cVMS) – octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), and dodecamethylcyclohexasiloxane (D6) – was evaluated in a typical secondary activated sludge wastewater treatment plant (WWTP). Water samples (influent, primary effluent, and final effluent) and sludge (primary sludge and waste activated sludge) samples were collected at overnight low, morning high, afternoon low, and evening high flows. Concentrations of cVMS in influents fluctuated with the influent flows, ranging from 0.166 to 1.13 μg L −1, 3.47–19.3 μg L −1, and 0.446–3.87 μg L −1 for D4, D5, and D6, respectively. Mass balance analysis of cVMS showed the average mass of D4, D5, and D6 entering and exiting the plant in influent and effluent, respectively, were 109 g d −1, 2050 g d −1, 280 g d −1, and 1.41 g d −1, 27.0 g d −1, 1.90 g d −1 . The total removal efficiency of cVMS was >96%. To elucidate their detailed removal mechanisms, Mackay's fugacity-based treatment plant model was used to simulate the fate of cVMS through the WWTP. Due to the unusual combination of high hydrophobicity and volatility of cVMS, volatilization in the aeration tank and adsorption to sludge were the two main pathways of cVMS removal from water in this WWTP based on the experimental and modeled results. The morning and evening high influent mass flows contributed almost equally at approximately 40% of the total daily cVMS mass, with D5 accounting for the majority of this daily loading. Graphical abstract: Highlights: Significant diurnal variability of cVMS in influents was observed. Morning and evening mass flows contributed major daily loading. Volatilization and adsorption were the two main removal pathways.